STUDI LITERATUR REVIEW: ANALISIS POTENSI BAHAYA K3 PADA PEKERJA TAMBANG MENGGUNAKAN JOB SAFETY ANALYSIS (JSA) PADAKEGIATAN PERTAMBANGAN - Puan Arliza Azmy; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
This research is motivated by dangerous events and risks that can occur in an industrial activity. Therefore, in order to obtain information about the hazards that may arise in a production, it is necessary to identify potential hazards. The activity of identifying potential threats in a work activity is carried out by the JSA method. Identification of potential threats in this research uses literature research methods, searches of national literature in the form of articles, journals and research. This research uses a comprehensive article search strategy in research journal databases and internet searches. The results of this study indicate that there are 36 identified hazards, the highest risks are in the loading phase of mining workers, namely dust exposure/inhalation, buried accidents and landslides. In the loading phase, during loading activities (transportation) is exposure/inhalation of dust, as well as in the unloading phase, namely subsidence due to underground collapse